Mcse training kit - Corporation, Microsoft ([S.l.] : Microsoft Press, 2001)
Microsoft Certified Professional (MCP) Exam 70-270 measures ability to install, configure, and administer Microsoft Windows XP Professional. With Readiness Review, certification candidates can sharpen their test-taking skills, save valuable time and money, and build their confidence for the real exam with the help of this exclusive exam simulation on CD-ROM.